An update on the effect of intra-articular intervention strategies using nanomaterials in osteoarthritis: Possible clinical application - Amirsaadat, Soumayeh; Amirazad, Halimeh; Hashemihesar, Ramin; Zarghami, Nosratollah (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis (OA) is the most common progressive condition affecting joints. It mainly affects the knees and hips as predominant weight-bearing joints. Knee osteoarthritis (KOA) accounts for a large proportion of osteoarthritis and presents numerous symptoms that impair quality of life, such as stiffness, pain, dysfunction, and even deformity. For more than two decades, intra-articular (IA) treatment options for managing knee osteoarthritis have included analgesics, hyaluronic acid (HA), corticosteroids, and some unproven alternative therapies. Before effective disease-modifying treatments for knee osteoarthritis, treatments are primarily symptomatic, mainly including intra-articular corticosteroids and hyaluronic acid, so these agents represent the most frequently used class of drugs for managing knee osteoarthritis. But research suggests other factors, such as the placebo effect, have an essential role in the effectiveness of these drugs. Several novel intra-articular therapies are currently in the clinical trial processes, such as biological therapies, gene and cell therapies. Besides, it has been shown that the development of novel drug nanocarriers and delivery systems could improve the effectiveness of therapeutic agents in osteoarthritis. This review discusses the various treatment methods and delivery systems for knee osteoarthritis and the new agents that have been introduced or are in development.